First results from the JWST early release science program Q3D: the fast outflow in a red quasar at z = 0.44 - Liu, Weizhe; Veilleux, Sylvain; Sankar, Swetha; Rupke, David; Zakamska, Nadia L.; Wylezalek, Dominika; Vayner, Andrey; Bertemes, Caroline; Ishikawa, Yuzo; Chen, Yu-Ching; Greene, Jenny E.; Heckman, Timothy; et al. (The astrophysical journal, 2025)
Quasar feedback may play a key role in the evolution of massive galaxies. The dust-reddened quasar F2M110648.35+480712 at z = 0.4352 is one of the few cases at its redshift that exhibits powerful quasar feedback through bipolar outflows. Our new observation with the integral field unit mode of the Near-infrared Spectrograph on board JWST opens a new window to examine this spectacular outflow through the Paα emission line with 3× better spatial resolution than previous work. The morphology and kinematics of the Paα nebula confirm the existence of a bipolar outflow extending on a scale of ∼17 × 14 kpc and with a velocity reaching ∼1100 km s−1. The higher spatial resolution of our new observation leads to more reliable measurements of outflow kinematics. Considering only the spatially resolved outflow and assuming an electron density of 100 cm−2, the mass, momentum, and kinetic energy outflow rates are ∼50-210 M⊙ yr−1, ∼(0.3-1.7) × 1036 dynes (∼14%-78% of the quasar photon momentum flux), and ∼​​​​​​(0.16-1.27) × 1044 erg s−1 (∼0.02%-0.20% of the quasar bolometric luminosity), respectively. The local instantaneous outflow rates generally decrease radially. We infer that the quasar is powerful enough to drive the outflow, while stellar processes cannot be overlooked as a contributing energy source. The mass outflow rate is ∼0.4-1.5 times the star formation rate, and the ratio of kinetic energy outflow rate to the quasar bolometric luminosity is comparable to the minimum value required for negative quasar feedback in simulations. This outflow may help regulate the star formation activity within the system to some extent.